Response Surface Methodology (RSM) For Process Parameters Optimization Of LiFePO4 Using Flame Spray Reactor For Li-ION Batteries - Na, Yong Sik (Universiti Sains Malaysia, 2021)
Lithium iron phosphate, LiFePO4 (LFP) is widely used due to the advantages it offers such as excellent reversibility, relatively safer than other lithium-ion batteries and its abundancy, which at the same time is inexpensive. In this final year project, the optimization of the process parameters for the synthesis of LFP via flame spray pyrolysis was done by implementing response surface methodology (RSM), a collection of mathematical and statistical techniques Which is a well-established method useful for approximating and optimizing processes. Design expert V11 was the software utilized for RSM. The first design used was the 1-factor D-optimal design to optimize the precursor concentration and obtain the statistical data of the available data, in which the optimum concentration of precursor was 0.35 M it would form a large particle which will then indirectly affect the discharge capacity. Then, effect of the two process parameters, namely calcination temperature and glucose content on the discharge capacity were studied, and its significance was determined based on the analysis of variance (ANOVA). Central composite design (CCD) was applied for the simulation of it and the optimized discharge capacity based on no specific criteria of the parameters was 160.417 mAh g-1 at a calcination temperature of 689.395 ℃ and the glucose content 26.2079 % and there are another 99 unique solutions. Then, as the criteria was set as minimum calcination temperature, minimum glucose content and minimum of both factors, the discharge capacity was 158.447 mAh g-1, 153.103 mAh g-1, 151.515 mAh g-1 respectively, all with only one unique solution. Lastly, three types of RSM, specifically, CCD, D-optimal design and historical data design were implemented and compared on which method would yield the best results, statistically.